Gut Microbiome-Modified Polyphenolic Compounds Inhibit α-Synuclein Seeding and Spreading in α-Synucleinopathies - Yamasaki, Tritia R.; Ono, Kenjiro; Ho, Lap; Pasinetti, Giulio M. (Frontiers in Neuroscience, 2020)
Misfolding, aggregation and deposition of α-synuclein (α-syn) are major pathologic characteristics of Parkinson’s disease (PD) and the related synucleinopathy, multiple system atrophy (MSA). The spread of α-syn pathology across brain regions is thought to play a key role in the onset and progression of clinical phenotypes. Thus, there is increasing interest in developing strategies that target and attenuate α-syn aggregation and spread. Recent studies of brain-penetrating polyphenolic acids, namely, 3-hydroxybenzoic acid (3-HBA), 3,4-dihydroxybenzoic acid (3,4-diHBA), and 3-hydroxyphenylacetic acid (3-HPPA) that are derived from gut microbiota metabolism of dietary polyphenols, show in vitro ability to effectively modulate α-syn misfolding, oligomerization and mediate aggregated α-syn neurotoxicity. Here we investigate whether 3-HBA, 4-hydroxybenzoic acid (4-HBA), 3,4-diHBA, or 3-HPPA interfere with α-syn spreading in a cell-based system. Using HEK293 cells overexpressing α-syn-A53T-CFP/-YFP, we assessed α-syn seeding activity using Fluorescence Resonance Energy Transfer (FRET) to detect and quantify α-syn aggregation. We demonstrated that 3-HPPA, 3,4-diHBA, 3-HBA and 4-HBA significantly attenuated intracellular α-syn seeding aggregation. To determine whether our compounds could inhibit brain-derived seeding activity, we utilized insoluble α-syn extracted from post-mortem MSA or PD brain specimens. We found that 3-HPPA effectively attenuated MSA-induced aggregation of monomer into high molecular weight aggregates capable of inducing intracellular aggregation. Outcomes from our studies suggest interactions between gut microbiome and certain dietary factors may form the basis for effective therapies that modulate pathologic α-syn propagation. Collectively, our findings provide the basis for future developments of probiotic, prebiotic, or synbiotic approaches for modulating the onset and/or progression of α-synucleinopathies.